Synthesis and Enzymatic Behaviour of Mono- and Dinuclear Complexes of Bivalent Transition Metal Ions with Schiff Base Derived from 2,6-Dibenzoyl-4-methylphenol and 2,6-Diaminopyridine - Chander, Jagdish; Kumar, Anil; Kumari, Sumona; Kumar, S.; Meera; Dhindsa, K.S. (Asian Journal of Chemistry, 2015)
The synthesis of Schiff base ligand 13,27-dimethyl-2,10,16,24-tetraphenyl-3,9,17,23,31,32-hexaazapentacyclo[26.3.1.14,8.111,15.118,22]-dotriaconta-1(28),2,4(31),5,7,9,11,13,15(30),16,18,20,22(32),23,25(29),26-hexadecaen-29,30-diol (H2L) and its mono- and dinuclear complexes with VO(IV), Mn(II), Co(II), Ni(II), Cu(II) and Zn(II) has been accomplished by both direct as well as template methods. The compounds have been characterized by elemental analyses, molecular weight determinations, molar conductance, room temperature magnetic moments, infrared, electronic and 1H NMR spectral data. The macrocyclic ligand complexes have been proposed to have distorted octahedral geometries around the metal ions. The mono- and dinuclear complexes have been evaluated for peroxidase-like activity.